The first mitochondrial genome of Creophilus Leach and Platydracus Thomson (Coleoptera: Staphylinidae: Staphylinini) and phylogenetic implications - Zhao, Tian-You; He, Liang; Xu, Xin; Chen, Zhen-Ning; Gao, Ya-Yue; Lü, Liang (Zootaxa, 2022)
Creophilus Leach and Platydracus Thomson are two genera whose members were formerly included in a poorly defined Staphylinus. Both include large-sized rove beetles that can be frequently found in carrion, faeces, and other such rotting materials worldwide. But there are not yet mitochondrial genomes in public databases, which deters scientists from further studies that involve species of these two genera. Here we present the first complete mitochondrial genomes of two typical Palaearctic species, Creophilus maxillosus and Platydracus impotens, which are also the first for the two genera. Additionally, we included the new mitogenomic data in a phylogenetic context using maximum likelihood phylogenetic analyses. Our results confirm the results of previous studies but show that the position of Creophilus, and therefore the monophyly of Staphylinina, could be affected by dataset constitution and model selection.